Protease production by different thermophilic fungi - Macchione, Mariana M. [UNESP]; Merheb, Carolina W. [UNESP]; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Humana Press Inc, 2008)
A comparative study was carried out to evaluate protease production in solid-state fermentation (SSF) and submerged fermentation (SmF) by nine different thermophilic fungi - Thermoascus aurantiacus Miehe, Thermomyces lanuginosus, T. lanuginosus TO.03, Aspergillus flavus 1.2, Aspergillus sp. 13.33, Aspergillus sp. 13.34, Aspergillus sp. 13.35, Rhizomucor pusillus 13.36 and Rhizomucor sp. 13.37 - using substrates containing proteins to induce enzyme secretion. Soybean extract (soybean milk), soybean flour, milk powder, rice, and wheat bran were tested. The most satisfactory results were obtained when using wheat bran in SSF. The fungi that stood out in SSF were T. lanuginosus, T. lanuginosus TO.03, Aspergillus sp. 13.34, Aspergillus sp. 13.35, and Rhizomucor sp. 13.37, and those in SmF were T. aurantiacus, T. lanuginosus TO.03, and 13.37. In both fermentation systems, A. flavus 1.2 and R. pusillus 13.36 presented the lowest levels of proteolytic activity.
Keywords: Protease; Thermophilic fungi; Solid state fermentation (SSF); Submerged fermentation; Wheat bran